PERAN MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN GLOBAL DI MTs BINA TARUNA MARELAN - Anggraini, Nadia; Saraini, Ihsan; Maghfiroh, Lusi; Febriyan, Rio (IKAMAS: Manajemen Pendidikan Islam, 2022)
Globalization brings a very significant change impact, especially on changes in the behavior of each individual. The link between globalization and education lies in the birth of a new society characterized by a "knowledge-based society" which is the basis of economic and political globalization which is constantly changing and requires a reflective attitude from humans, namely the ability to reflect on life based on ratios. For this reason, education is very important in realizing a future society based on science. The purpose of this study was to find out how the role of Islamic educational institution management in facing global challenges at MTs Bina Taruna Marelan school. This research uses a qualitative approach with the type of case study research. Data collection is done by observation, interviews, and documentation. The results of this research at MTs Bina Taruna Marelan are: (1) Challenges of Globalization of Management of Islamic Educational Institutions at MTs Bina Taruna Marelan; (2) Management Model of Islamic Education Institutions at MTs Bina Taruna Marelan; (3) The Impact of Globalization on Education Management at MTs Bina Taruna Marelan.